Between and Betwixt the Other Theatre and the Theatre of the Other:: Performativity as (Re)presenting, Show and Self-Awareness in the Myth of Barba - Kavouras, Pavlos (Conatus - Journal of Philosophy, 2023)
This article deals with the legendary figure of Eugenio Barba as a paradigmatic case to demonstrate the difference between the other theatre and the theatre of the other. Its main objective is to discuss the juxtaposition of performativity as (re)presenting, showing, and self-awareness by narrating the myth of Barba. The argument is presented through six interconnected caveats: the legend and its myth; The Moon rises from the Ganges: the story inside the myth; the critique of western civilization: an insider’s story of self-reflexivity; the other theatre is not the theatre of the other; the life-world of the myth of Barba; and finally, performing otherness, othering performance. The article is addressed mainly but not exclusively to readers with a background in cultural anthropology, performance studies, theater studies, hermeneutics, phenomenology, history of civilization, literary theory, colonialism, and representation of the other.